Role of iron metabolism in pulmonary tuberculosis: a case control study in Katra - Sharma, Chandan; Badyal, Ashima (International Journal of Scientific Reports, 2021)
Background: Tuberculosis (TB) disease still carries an appreciable mortality, representing the world’s second leading cause of death from a single infectious agent. In a living organism, iron (Fe) is an essential micronutrient, as a co-factor of enzymes and involved in various cellular functions. Fe homeostasis is maintained by various mechanisms is disturbed in diseased. The aim of study was estimating the Fe metabolism in pulmonary tuberculosis patients in relation to sputum bacterial load and inflammation and severity. Methods: This present case control study was conducted in department of medicine CHC Katra, Jammu, Jammu and Kashmir from June 2019 to September 2019. A total of 100 adult patients diagnosed with pulmonary TB (PTB) and 74 healthy, age matched individuals were included in the study. Results: Out of 100 patients, 65% were males with average age being 43.56±15.63 years. Mean serum protein at 6.32±0.78 g/dl and mean serum albumin at 3.45±0.52 g/dl showed significance. Mean serum Fe (39.68±18.32 ug/dl) and mean hemoglobin level (9.36±1.52) was significantly lower as compared to controls. Serum TIBC, serum ferritin and serum CRP showed higher values among cases. Raised serum ferritin levels corresponded to the raised CRP and TB is seen causing significantly low levels of transferrin. Conclusions: CRP and ferritin should be regarded as useful markers of PTB activity and also to the risks associated to it and also while monitoring therapeutic response.